2011
DOI: 10.1111/j.1464-5491.2010.03203.x
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of symptomatic and asymptomatic hypoglycaemia in Type 1 diabetes: effect of impaired awareness of hypoglycaemia

Abstract: Adults with Type 1 diabetes who have impaired awareness of hypoglycaemia are exposed to a much higher incidence of asymptomatic hypoglycaemia than those with normal awareness and are at higher risk of developing severe hypoglycaemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
25
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 15 publications
4
25
0
Order By: Relevance
“…The study of Östenson et al (2014) reported that respondents with impaired awareness had significantly higher nonsevere hypoglycemic event rates than those who were aware. A number of previous studies have shown a statistically significant increase in severe hypoglycemic events in patients with reduced awareness (Nazar et al, 2016; Weitgasser & Lopes, 2015; Schopman, Geddes & Frier, 2011; Choudhary et al, 2010; Smith et al, 2009; Geddes et al, 2008). Kulzer, Seitz & Kern (2014) found a significant correlation between awareness of hypoglycemia and asymptomatic, nonsevere hypoglycemic events.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The study of Östenson et al (2014) reported that respondents with impaired awareness had significantly higher nonsevere hypoglycemic event rates than those who were aware. A number of previous studies have shown a statistically significant increase in severe hypoglycemic events in patients with reduced awareness (Nazar et al, 2016; Weitgasser & Lopes, 2015; Schopman, Geddes & Frier, 2011; Choudhary et al, 2010; Smith et al, 2009; Geddes et al, 2008). Kulzer, Seitz & Kern (2014) found a significant correlation between awareness of hypoglycemia and asymptomatic, nonsevere hypoglycemic events.…”
Section: Discussionmentioning
confidence: 98%
“…This same literature also refers to impaired awareness of hypoglycemia in people with type 2 diabetes (Banck-Petersen et al, 2007; Clarke et al, 1995) which can increase the risk of severe hypoglycemia (Moghissi, Ismail-Beigi & Devine, 2013). A number of previous studies have shown a statistically significant increase in severe hypoglycemic events in patients with reduced awareness (Weitgasser & Lopes, 2015; Schopman, Geddes & Frier, 2011; Choudhary et al, 2010; Smith et al, 2009; Geddes et al, 2008; Clarke et al, 1995). The study by Rondags et al (2015) showed that hypoglycemia awareness significantly reduces severe hypoglycemia episodes.…”
Section: Introductionmentioning
confidence: 98%
“…Further, assessment of alcohol use and hypoglycemia-related WCB such as skipping meals is encouraged since they are known to be associated with hypoglycemia. 15 , 18 …”
Section: Discussionmentioning
confidence: 99%
“…126 All aimed to foster improved symptom recognition and self-treatment practices and all were predicated on data showing that impaired hypoglycaemia awareness could be induced/reversed by hypoglycaemia exposure/avoidance [127][128][129][130][131][132] and increased the risk of severe hypoglycaemia sixfold. 133 Although all had led to some improvements, none had resulted in full restoration of awareness or obliteration of severe hypoglycaemia. Our curriculum built on the reported interventions tested in these studies but included psychological strategies to identify and address the specific unhelpful cognitions maintaining impaired hypoglycaemia awareness informed by our own qualitative research.…”
mentioning
confidence: 99%